ETHICS, WRITING, AND READING OF HISTORY: THE PROBLEMS OF EXPECTATION AND TRUST - Munhoz Ohara, Joao Rodolfo [UNESP] (Univ Sao Paulo, Fac Filosofia Letras & Ciencias Humanas, 2019)
The functioning of truth in a history text does not depend only on its epistemological conditions, but also on an ethical relation between the historian and the reader. Paul Ricoeur proposed that such ethical relation is based upon a tacit reading pact, a contract in which the author ensures his reader that his narrative is true. On the other hand, Michel de Certeau has worked both with the internal functioning of the machinery that produces truth (the historiographical operation) and with the active character of the reading process. As such, I propose that one should engage with this ethical relationship between author and reader, and that such engagement can benefit from a reflection on the categories of trust and expectation.
Keywords: History writing; history reading; ethics; trust; expectation